Safety, Satisfaction, and Settlement in Domestic Relations Mediations: New Findings. (October 2016) - Raines, Susan; Choi, Yeju; Johnson, Joshua; Coker, Katrina
Abstract : Researchers and mediators have long been concerned about coercion, intimidation, and safety threats that could occur in mediation for cases where previous violence between the parties has occurred. Most of the research focuses on screening tools to identify parties at risk. When parties screen positive for intimate partner violence (IPV), some proceed to mediation and some do not, depending on the policies of individual mediation programs. But this misses a step: Some cases may benefit from mediation while others won't, but how can we predict whether mediation will be useful and safe in specific instances? This study uses survey data obtained from parties in domestic relations mediations to examine issues of safety, satisfaction, and settlement in the presence of various IPV behaviors. Key Points for the Family Court Community: Screening for intimate partner violence (IPV) is not enough. Research is needed to help direct us toward those cases which might benefit from mediation, even in the presence of IPV, and which would not benefit. Some violent or threatening behaviors have a greater impact on settlement rates and satisfaction levels than others. Previous verbal threats to harm the other party had a greater negative impact on the chance of settlement than did a history of physical violence between the parties. Mediators and court personnel who are engaged in screening cases for violence and safety need better, specific guidance about which types of past behavior are likely to reduce the benefits of mediation for all concerned.